Agent based modelling as a decision support system for shadow accounting - Chesney, Thomas; Gold, Stefan; Trautrims, Alexander (Elsevier, 2017)
We propose the use of agent based modelling to create a shadow account, that is, a secondary account of a business which is used to audit or verify the primary ac¬count. Such a model could be used to test the claims of industries and businesses. For example, the model could determine whether a business is generating enough funds to pay minimum wage. Parameters in the model can be set by observation or a range of values can be tested to determine points at which enough revenue could be generated. We illustrate the potential of agent based modelling as a tool for shadow accounting with a case study of a car wash business.